Spontaneous subarachnoid hemorrhage as the primary manifestation of carotid cavernous fistulas: case report - Clement Hamani; Almir Ferreira Andrade; Eberval Gadelha Figueiredo; Orildo Ciquini Jr.; Raul Marino Jr. (Arquivos de Neuro-Psiquiatria)
We report the case of a 19-year old male patient initially admitted to our service after a motor vehicle accident with a normal neurologic evaluation and a CT scan that revealed no abnormalities. Nineteen months later, he was readmitted after a subtle headache episode, followed by a brief loss of consciousness. He was submitted to a complete evaluation, which revealed no abnormalities (even in the neurologic and ophthalmologic exams). A CT was performed revealing a diffuse subarachnoid hemorrhage. Contrast enhancement displayed a right paraselar lesion, which was first interpreted as a giant aneurysm. The patient underwent a cerebral angiography which showed a right carotid-cavernous fistula with retrograde venous drainage through the superior and inferior petrosal sinuses. Filling of various cortical vessels was observed. The patient was treated with endovascular technique and a control angiographic study assured the complete closure of the fistula. He had an excellent clinical recovery, being discharged in good conditions.